Association between Diabetes Knowledge and Self-Efficacy in Patients with Type 2 Diabetes Mellitus in China: A Cross-Sectional Study. (25th September 2020) - Qiu, Tieying; Huang, Jin; Wang, Weixing
Abstract : Objective . This study aimed to explore the association between DM knowledge and self-efficacy in Chinese patients with T2DM. The influence factors for DM knowledge were explored, and evidence on interventions was provided to patients for information. Design . A cross-sectional survey was conducted in various hospitals in Hunan Province, China, from April 2017 to February 2019, by using multistage stratified randomized sampling. DM knowledge and self-efficacy were measured using the Audit of Diabetes Knowledge (ADKnowl) and the General Self-efficacy (GSE) Scale. The relationship between the ADKnowl and the GSE scores was analyzed using the Spearman correlation analysis. Differences in the ADKnowl and GES scores among groups with different sociodemographic characteristics were computed; significant variables and GES scores were input in the multiple stepwise linear regression model to predict the influencing factors of ADKnowl scores. Results . A total of 1, 512 eligible patients with T2DM were included in this study, and their mean ADKnowl score was 59.04 ± 16.24. The top score of the eight dimensions in the ADKnowl scale was reducing the complication risk by 71.01%. The mean GSE score was 2.42 ± 0.59. The Spearman correlation analysis showed that the GSE score displayed a significantly positive correlation with DM knowledge at the ADKnowl scale ( r  = 0.172, P < 0.001 ). The best fit multivariable linear regression analysis revealed eight variables that explained 37.6% of the variance of ADKnowl scores. They were diabetes-learning experience, educational background, complication, therapy, waist-to-hip ratio, diabetes duration, marital status, and GSE ( R 2  = 0.376, F  = 5.971, P = 0.015 ). Conclusions . In Chinese patients with T2DM, the self-efficacy in managing DM positively influenced DM knowledge. DM knowledge, as a protective factor, conversely improved the efficiency of self-management for T2DM. Some ignored influence factors in previous studies can be showed by investigating and analyzing from two scales. Health educators and promoters should help in developing DM knowledge and self-efficacy.